Perceived effects of home environment to selected UP Diliman students' motivation in studying - Bosmion, Jinny Bea B. (College of Home Economics, University of the Philippines Diliman, 2019)
This study described the study home environment of selected college students in the University of the Philippines Diliman. It also determined the perceived contribution of physical and social home environment to students' motivation to study. A total of 30 college students, purposively selected, participated in the research. A qualitative interview guide was used to describe the students' home environment as well as its effects on their study motivation. Data from the interview were analyzed using thematic analysis, descriptive statistics, and qualitative descriptions. Results show that most facilities, fixtures, and good interior environment conditions are provided to the students at home except for quiet study areas, view of the outdoors, and tidy and organized surroundings. The most common aspects that motivate students to study include good interior ambiance, availability of facilities, and the availability of study needs; while uncomfortable and unorganized interior surroundings, distracting facilities, and lack of efficient facilities, privacy and personal space are aspects that demotivate them. In terms of social home environment, the students' parents are found to be generally supportive and encouraging. On the contrary, sibling support in relation to studying is generally low to average, even though their overall relationship with their siblings is good. . Furthermore, care and assistance, affective communication, freedom, and respect from parents and siblings are among the social home environment factors that motivate students to study; while pressure, comparison, lack of sensitivity, disturbance and time-intensive distractions are aspects that demotivate them. Finally, results show that household tasks and rules at home have both positive and negative effects on study motivation. The study recommends teaching and strengthening Home Economics instruction in elementary and high school in order for students to learn efficient time and space management that will further enhance their study home environment.